Influence of World Military Expenditure and Inflation on Indonesia’s Economic Growth Period 1992–2022 - Himawan, Aldi; Tumanggor, Muliahadi; Prakoso, Lukman Yudho; Suwito, Suwito (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Military expenditure plays an important role in state spending to maintain security and defense as well as economic stability. The increase in world military expenditure is triggered by global geopolitical threats. Inflation management has an impact on economic growth in addition to military expenditure. It is interesting to look at how Indonesia's economy has grown in the current global environment, which is marked by geopolitical unpredictability ranging from the war between Russia and Ukraine to the financial crisis and the COVID-19 pandemic. The purpose of this study is to look into how inflation and World military expenditure affected Indonesia's economic growth from 1992 and 2022. This study employed descriptive and inferential quantitative research methodology, concentrating on secondary data obtained from statista.com, the World Bank, the Stockholm International Peace Research Institute, and the Central Bureau of Statistics. The findings indicate that inflation and world military expenditure have a substantial impact on Indonesia's economic growth. According to each variable, Indonesia's economic growth is significantly and negatively impacted by inflation, while it is not significantly and negatively impacted by military expenditure. Military expenditure is influenced by geopolitical unpredictability, which can impede sustained economic expansion. Furthermore, whereas high inflation creates economic uncertainty, a stable inflation rate fosters economic growth. World military expenditure ought to present prospects for the defense industry to be stimulated in ways that boost sales and new technological advancements in military hardware designed to be globally competitive with defense industries in other nations through defense budget assistance. To lower production costs in the defense industry and other supporting businesses, the government must also continue to implement the target inflation rate.